Implementasi Pendidikan Anak Usia Dini Berbasis Ramah Anak dalam Meningkatkan Kualitas Pembelajaran: Studi Literatur - Fahmi; Andinda Saadah; Siti Saskia Asifa; Nabiela Azzah Atiqoh; Selvi Ulandari; Sulastri; Suci Amanda (Kartika: Jurnal Studi Keislaman, 2026)
This study is motivated by the persistence of problems in the management of Early Childhood Education (PAUD) institutions, particularly in aspects of management that affect the quality of children's learning. The increase in access to PAUD has not been fully followed by improvements in service quality, especially in planning, organizing, implementing, and evaluating learning. The research problem focuses on how the implementation of PAUD management can improve the quality of early childhood learning. This study uses a descriptive qualitative approach aimed at understanding PAUD management practices in the field. Data were obtained through a literature study from various relevant scientific journals. The results show that proper management implementation has a significant influence on learning quality, especially in creating a structured learning environment that meets children's developmental needs. However, there are still gaps between ideal concepts and actual practices, such as limited teacher competence, suboptimal administrative systems, and lack of continuous evaluation. Therefore, efforts are needed to improve human resource capacity and strengthen management systems so that the quality of early childhood learning can be improved